Competition policy as countervailing power and monopoly power in global value chains - Reiner, Christian (Momentum Quarterly, 2023)
Global value chains (GVC) are a central element of capitalism in the epoch of hyperglobalisation. They are governed by lead firms from global economic centres, and suppliers in the global south produce and deliver goods and services according to their specifications. Benefits are, however, shared very unevenly along the GVC. One important reason for this is the unequal distribution of monopoly power between the different firms. The article discusses the means by which a reduction in these power imbalances could be accomplished. Using markup developments, profit rates and measures of industry concentration, it is demonstrated how lead firms in the global North have been able to expand their power in output markets and input markets at the expense of supplier firms in the global South. I argue that institutional and technological barriers to entry, for instance due to a rising importance of intangible assets, have helped to protect the dominant position of lead firms in GVC. The logical economic response would be the build up of a countervailing power in the global South. A critical evaluation of cartels, cooperatives, regional integration, and competition policy indicates their potential to reduce the exploitation of suppliers in the periphery yet any articulation and realization of an effective countervailing power is complex and unlikely to remain unchallenged by powerful lead firms and the governments of their home countries.
Keywords: Global value chains; monopoly power; rent-seeking; countervailing power; competition policy